The Contribution of Calcium to Changes in Leaf Anatomical Character of Oil Palm Seedlings (Elaeis guineensis Jacq.) under Drought Stress - Novi Yulanda Sari; Eka Tarwaca Susila Putra (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
The research was purposed (1) to know the effects of drought stress on changes in leaf anatomical character of oil palm seedlings (2) to know the contribution of calcium in cell compactness and increase the structural strength of leaf tissue so that oil palm seedlings were more tolerant to drought stress. This experiment was laid out following a split plot design with three blocks as replication. Main plot consists of drought stress levels, that are field capacity (FTSW 1.00), moderate drought stress (FTSW 0.35) and severe drought stress (FTSW 0.15). The fraction of transpirable soil water (FTSW) is a method for evaluating gradually increasing drought stress based on the amount of water loss due to transpiration. Meanwhile, subplot consists of four doses of calcium (Ca), that are of 0.0 g/seedlings, 0.04 g/seedlings, 0.08 g/seedlings, and 0.12 g/seedlings. Calcium fertilizer used is calcium sulfate (CaSO4) pure analysis. Leaf anatomical character was observed including the epidermal length and epidermal width; hypodermal length and hypodermal width; palisade cell length and palisade cell width; sponge cell length and sponge cell width; mesophyll tissue thickness; xylem and phloem diameter. The results showed that moderate and severe drought stress reduced epidermal cell length, upper hypodermal cell width, mesophyll thickness, palisade width and phloem diameter of leaf vessels. The applications of calcium to the leaf of oil palm seedlings under drought stresses were able to increased in the sponge cell length at a Ca dosage of 0.04 g/seedlings; increased lower hypodermal width and diameter phloem at a Ca dosage of 0.04 g/seedlings; and increased diameter xylem of leaves vessel at a Ca dosage of 0.12 g/seedlings.